Pengaruh Promosi Media Sosial dan Kesadaran Halal terhadap Keputusan Pembelian Produk Makanan Kekinian pada Generasi Z di Kota Pekanbaru - Yusnidar Via Arnanda; Ahda Segati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The development of digital technology and social media has had a significant influence on consumer behavior in purchasing products, especially trendy food products. Social media has become an effective promotional tool because it is able to reach consumers widely and provide product information quickly. However, consumers’ purchasing decisions are not only influenced by promotions through social media, but also by other factors such as halal awareness.This study aims to determine the effect of social media promotion and halal awareness on purchasing decisions. The research method used is a quantitative method with data collection techniques through distributing questionnaires to 100 respondents who have purchased trendy food products through social media. The data obtained were then analyzed using multiple linear regression analysis with several testing stages, namely validity test, reliability test, classical assumption test, t-test, and F-test.The results of the study indicate that social media promotion has a positive and significant effect on purchasing decisions, while halal awareness does not have a significant effect on purchasing decisions. Simultaneously, social media promotion and halal awareness influence purchasing decisions with a coefficient of determination value of 0.235, which shows that 23.5% of purchasing decisions can be explained by these two variables. Based on these findings, it can be concluded that social media promotion is the main factor influencing consumers’ purchasing decisions.